y-3=6(x+1)

Simple and best practice solution for y-3=6(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-3=6(x+1) equation:


Simplifying
y + -3 = 6(x + 1)

Reorder the terms:
-3 + y = 6(x + 1)

Reorder the terms:
-3 + y = 6(1 + x)
-3 + y = (1 * 6 + x * 6)
-3 + y = (6 + 6x)

Solving
-3 + y = 6 + 6x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + y = 6 + 3 + 6x

Combine like terms: -3 + 3 = 0
0 + y = 6 + 3 + 6x
y = 6 + 3 + 6x

Combine like terms: 6 + 3 = 9
y = 9 + 6x

Simplifying
y = 9 + 6x

See similar equations:

| 3(4m-5)=124m | | 2*x+1=2+2x | | (15b-1)-7(2b+2)=-6 | | 7x+4x+3+9=6x+3+4x | | x+7*2=3x+5 | | 10b+3+4= | | 12-7x=6x+11 | | 96+122=180 | | x+(x-48700)=284790 | | f(4)=10-.25*4 | | -9+5x=-9 | | 7x+5=7-7x | | 6x+12=-28-4c | | 7x^2+6=17x-5 | | 6x+9+7y-2x+3= | | 8+6x=-22+x | | 4x-8+3x=60-2x+3x | | t*4-4=11 | | P^2=5p+84 | | 10y-3=8y+7 | | x+88+127=180 | | 3-2(2-x)=8 | | x+88=127 | | 88+127=x | | 2x+3(x+3)=x+3 | | 3.02+d=2.91 | | 4n+8n= | | 13000.00+25000x=27500x | | x+66=117 | | 3x^2+48x-300=0 | | .12x+x=273.16 | | 4(x-3)+4=21 |

Equations solver categories